Media report about climate change in an English online Malaysian newspaper through thematic and discourse analysis approaches - Tasha Erina Taufek; Nor Fariza Mohd Nor; Azhar Jaludin; Sabrina Tiun; Lam, Kuok Choy; Jamaluddin Aziz (Penerbit Universiti Kebangsaan Malaysia, 2022)
Climate change studies are mainly focused on disaster management and inundated with scientific jargons that the public could not fathom. Thus, the dissemination of climate change discourse to the public has been less effective due to lack of information and understanding which explains the lack of public engagement and participation. Studies on climate change that consider linguistics aspects are beginning to emerge, but are still lacking. Therefore, the present study intends to conduct a linguistic analysis by identifying themes in news on climate change and by analysing the extent of media propagation about climate change. 922 news articles from Malaysiakini were analysed using a corpusdriven approach through frequency and collocation analysis. This enabled us to identify themes on climate change. Discourse analysis was then conducted to find out about the linguistic manifestations of the identified themes. The findings reveal that governance is the most propagated theme, followed by mitigation and adaptation, contributor and impacts, and threats, which may polarise the public’s understanding of climate change. Instead, the themes of contributors and impacts, and threats are those which should be put forward as they may provide facts on the causal relationship of climate change that may help in assisting the public in understanding what to do, what to avoid, and the consequences of not acting on climate change. An understanding of the temporal aspects of public involvement in engaging with climate change issues through thematic analysis could assist in identifying the types of public participation in this issue.